THE PALLAQUERAS OR CCORI ÇAPA KOYA - Cazorla Zen, Carmen (2012)
An unknown woman activity in same place of Peru is a work with waste mine. The Untuca Pallaquera is a very special example for a study of particular woman economy in inhospitably place, and a question about origin is possible in pre-colonial times.